Screening of Latent Tuberculous Infection (LTBI) before starting anti-tumor necrosis factor therapy in patients with psoriasis: A primer for clinical dermatologist - Swetalina Pradhan; Bhushan Madke; Shekhar Neema; Poonam Kabra; Adarsh Lata Singh; Sangita Yadav (Wolters Kluwer Medknow Publications, 2021)
Anti-tumor necrosis agents are being increasingly used in the management of moderate to severe psoriasis. Therapy with antitumor necrosis factor alpha (TNF-α) agents is being fraught with reactivation of latent tuberculosis infection (LTBI). This paper addresses the intricate relation between LTBI and anti-TNF-α agents and provides working guidelines for screening of LTBI and its management before prescribing anti-TNF-α therapy in patients with psoriasis.